Use of a Non-Crosslinked Collagen Membrane During Guided Bone Regeneration Does Not Interfere With the Bone Regenerative Capacity of the Periosteum - Pinotti, Felipe Eduardo [UNESP] (2018)
Purpose: To assess whether the use of a non-crosslinked porcine collagen type I and III bi-layered membrane inter-positioned between the periosteum and a bone defect would interfere with the bone regenerative capacity of the periosteum. Materials and Methods: Sixty rats, each with 1 critical-size calvarial defect (CSD; diameter, 5 mm) in the parietal bone, were randomly allocated to 1 of 3 equal-size groups after CSD creation: 1) the periosteum was excised and the flap was repositioned without interposition of a membrane (no-periosteum [NP] group); 2) the flap including the periosteum was repositioned (periosteum [P] group); and 3) a non-crosslinked collagen membrane was inter-positioned between the flap, including the periosteum, and the bone defect (membrane [M] group). Micro-computed tomography, qualitative histology, immunohistochemistry, and reverse transcription real-time quantitative polymerase chain reaction were performed at 3, 7, 15, and 30 days postoperatively. Results: A markedly increased radiographic residual defect length was observed in the NP group compared with the P group at 30 days. The NP group also presented a smaller radiographic bone fill area than the P group at 15 and 30 days and then the M group at 30 days. The P and M groups exhibited considerably greater expression of bone morphogenetic protein-2 and osteocalcin than the NP group at 7 days; expression of transforming growth factor-β1 was considerably greater in the NP group at 15 days. Further, the P group presented considerably higher gene expression levels of Runx2 and Jagged1 at 7 days and of alkaline phosphatase at 3 and 15 days compared with the M and NP groups. Conclusion: Interposition of this specific non-crosslinked collagen membrane between the periosteum and the bone defect during guided bone regeneration interferes only slightly, if at all, with the bone regenerative capacity of the periosteum.